Penyuluhan Pembangunan Sumur Resapan Air Hujan di Kelurahan Cempaka Kecamatan Cempaka Kota Banjarbaru - Akhmad Gazali; Fathurrahman Fathurrahman (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
The construction of the well percolating rainwater is one of the efforts to improve the sustainability of groundwater. Increased knowledge and awareness of the population about the importance of the well percolating as an effort of conservation of groundwater and prevent floods, as well as the knowledge and skills to make the well percolating the Sepik high, cheap, and easily carried out by the population is a goal to be achieved in the activities of this community. Extension building of the well-percolating rainwater in the village of Cempaka is done by the method of questioning accompanied by lectures, and demonstrations. Lecture method is required to explain the efforts of the management and sustainability of water resources as well as the existence of the well percolating in General, while questioning provided an opportunity for participants to better understand the concepts so that those who are not yet familiar with can ask. Method demonstration is required to clarify the process of building the well percolating rain. As for the obstacles faced was the lack of understanding of the people about the well-percolating rainwater because of the varied educational background, expensive running costs of making the well percolating, and lack of public awareness about the sustainability of groundwater. Some of the benefits that can be gained from this outreach activity participant, among others, can understand the function of the forest, understanding the function of the sustainability of the land, and know the techniques of making a well-percolating rainwater with functions/benefits.